INCREASING KNOWLEDGE OF DAARUT TAUHIID BANDUNG GOLDEN ISLAMIC BOARDING SCHOOL PROGRAM PARTICIPANTS THROUGH PROJECT-BASED LEARNING - Ruhmawati, Tati; Kamsatun, Kamsatun; Yulianto, Bambang; Saepudin, Asep (Universitas Pendidikan Indonesia (UPI), 2022)
SDGs target number 3.4 in 2030 reduces by one third the premature death rate from non-communicable diseases (PTM). The elderly are very at risk of experiencing PTM such as hypertension, heart disease, diabetes, stroke, rheumatism, and others.Method: This type of research is quasi experiment with pre-posttest group design without control. The intervention provided is in the form of project-based learning. The population is the students of the Golden Age of Daarut Tauhiid Bandung as many as 19 people. Data collection techniques using a questionnaire sheet. Respondents measured knowledge before and after participating in learning. The data that has been collected is then processed and analyzed using the dependent T test.Results: The average score of respondents' knowledge before learning was 71 and after learning was 82. The results of the dependent T test obtained a value of p = 0.003 less than α (0.05), which means that there were differences in the knowledge of respondents before and after project-based learning was carried out.Conclusion: Project-based learning can increase respondents' knowledge about symptoms, how to prevent and treat non-communicable diseases (PTM) by 13.4%.